H σολωμική ars excerpendi και η ανασύσταση της εικονικής βιβλιοθήκης του ποιητή: Η περίπτωση των γαλλικών σημειώσεων-παραθεμάτων στα χειρόγραφα των Ελεύθερων πολιορκισμένων - Παύλου Κωστής (Σύγκριση/Comparaison/Comparison, 2025)
Solomos’s ars excerpendi and the reconstruction of the poet’s virtual library: the case of the French notes-citations in the manuscripts of The Free Besieged Launching from the foundational principles of genetic criticism regarding an author’s library, this article examines the material traces of writing in the manuscripts of Dionysios Solomos’s The Free Besieged. Its objectives are twofold: first, to explore the connection between Solomos’s ars excerpendi and the reconstruction of his virtual library; second, to identify and analyse the explicit or implicit French notes-citations within the manuscripts, which reveal Solomos’s multilingualism as a reader and copyist. The discussion begins by providing an overview of key issues related to the concept of an author’s virtual library and its genetic implications, along with a clarification of essential terminology. The article then examines the reconstruction of Solomos’s virtual library, emphasising the necessity of this process to uncover the interplay and creative dialogue between the reading material and the process of writing reflected in the manuscripts. Next, an effort is made to organise and systematise the key elements of Solomos’s multilingual ars excerpendi. This is followed by a review of prior identifications of French notes-citations in his manuscripts, alongside the presentation of new discoveries. These findings are complemented by a comprehensive presentation of the historical and bibliographical information concerning the printed sources from which these notes-citations are drawn, as well as a concise biographical note of their authors. The study concludes with a comprehensive appendix that consolidates the entire material.